2020
DOI: 10.3389/fpubh.2020.00493
|View full text |Cite
|
Sign up to set email alerts
|

Use of a Spinal Thermal Massage Device for Anti-oxidative Function and Pain Alleviation

Abstract: Background: Elderly people are vulnerable to a variety of diseases, including chronic pain, which reduces their levels of physical fitness. Thermal massage has been shown to relieve pain and activate antioxidant enzymes. The objective of this study was to determine whether thermal massaging of the spinal column can reduce muscle pain and induce antioxidant function. Methods: This study included participants aged ≥60 years with lower back pain. The participants were assigned to either an experimental group who … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
13
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(18 citation statements)
references
References 34 publications
(36 reference statements)
5
13
0
Order By: Relevance
“…Moreover, our findings suggest that blood flow can be increased four-fold at depths of 2-3 cm, corresponding to the lumbar musculature. These findings are consistent with clinical observations performed with the same thermo-mechanical massage bed (4–6, 12).…”
Section: Introductionsupporting
confidence: 92%
See 2 more Smart Citations
“…Moreover, our findings suggest that blood flow can be increased four-fold at depths of 2-3 cm, corresponding to the lumbar musculature. These findings are consistent with clinical observations performed with the same thermo-mechanical massage bed (4–6, 12).…”
Section: Introductionsupporting
confidence: 92%
“…The basis of this finding is that blood flow increases quickly and saturates at in situ temperature gradients of approximately 3° (7). Specifically, our FEM model predicts that such temperature increases are attainable at depths of 2 to 3 cm with actuator temperatures between 55° and 65°, values that overlap with those tested in earlier studies (5, 6). Thus, despite the exponential decay of temperature with depth (Figure 2), there is a sufficient gradient produced at the depths occupied by muscle tissue (1.5 - 5.5 cm) to modulate blood flow to the muscles of the lumbar region, which represent a common target of therapeutic massage beds.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…It is further shown that the mechanical traction delivered by this system is effective in a broad range of BMI subjects, and it is directly proportional to the set traction level of the therapy. In addition, tensile stresses produced by this device in the disc tissue can explain clinical observations using the same automatic message devices modeled here on immune status [6], autonomic function [10], inflammation[50, 51], pain [6-9, 52, 53], intervertebral space changes [37], and activate antioxidant enzymes [7].…”
Section: Discussionmentioning
confidence: 99%
“…These approaches may be followed by complementary techniques such as acupuncture, transcutaneous electrical nerve stimulation (TENS), physical therapy, spinal manipulation/mobilization, spinal injections, spinal traction and surgery. Mechanical based approaches are generally used for therapeutic purposes including management of pain [6][7][8][9], relaxation / autonomic health [10], enhancing local circulation [11][12][13][14][15][16][17], and recovery from fatigue [11,16,[18][19][20].…”
Section: Introductionmentioning
confidence: 99%